De la Réforme Agraire à la Loi Indienne de 1972. Le peuple mapuche et l’Unité Populaire (Chili, 1970-1973) - Daniela Durán Cid (Nuevo mundo - Mundos Nuevos, 2020)
During the process of Chilean agrarian reform (1964-1973), the peasant's demand for access to land opened the way for an old Mapuche reivindication for the recovery of the “usurped” lands, initiated with the military expansion of the Chilean nation-state in the 19th century. The Mapuche political organizations of the late 1960s succeeded in placing the demand at the center of the transformations promoted by the Agrarian Reform, a reform that aimed to modify the land tenure structure in Chile. In this regard, the Popular Unity government (1970-1973) was particularly attentive to this demand and tried to generate instances to respond to it, mainly through a project of Indigenous Law that gathered the requests of Mapuche organizations, which finally resulted in the promulgation of Law n°17729 in 1972. In this article we will delve into this particular episode in the recent history of relations between the Chilean state and the Mapuche people, analyzing how the political tensions of the time and the political-ideological debates inherent to the Agrarian Reform permeated the indigenous question.